2017
DOI: 10.1104/pp.17.01181
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen for Impaired Systemic RNAi Highlights the Crucial Role of DICER-LIKE 2

Abstract: Posttranscriptional gene silencing (PTGS) of transgenes involves abundant 21-nucleotide small interfering RNAs (siRNAs) and lowabundance 22-nucleotide siRNAs produced from double-stranded RNA (dsRNA) by DCL4 and DCL2, respectively. However, DCL2 facilitates the recruitment of RNA-DEPENDENT RNA POLYMERASE 6 (RDR6) to ARGONAUTE 1-derived cleavage products, resulting in more efficient amplification of secondary and transitive dsRNA and siRNAs. Here, we describe a reporter system where RDR6-dependent PTGS is initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
94
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 54 publications
6
94
1
2
Order By: Relevance
“…Moreover, DCL2 is 484 required to respond to mobile signals for systemic PTGS (Fig. 9), supported by a recent 485 report of a critical role of DCL2 in systemic PTGS in Arabidopsis (Taochy et al, 2017).…”
supporting
confidence: 51%
See 3 more Smart Citations
“…Moreover, DCL2 is 484 required to respond to mobile signals for systemic PTGS (Fig. 9), supported by a recent 485 report of a critical role of DCL2 in systemic PTGS in Arabidopsis (Taochy et al, 2017).…”
supporting
confidence: 51%
“…9). Taochy et al (2017) 494 have elegantly shown that Arabidopsis DCL2 is required in both the source rootstock and 495 recipient shoot tissue for RDR6-dependent systemic PTGS, although this latest discovery is 496 in contrast to their previous finding (Brosnan et al, 2007). as RNAi of DCL4 or DCL3 enhances systemic PTGS in distant young leaves (Fig.…”
contrasting
confidence: 41%
See 2 more Smart Citations
“…The DCL2 protein processes double-stranded RNA (dsRNA) molecules of exogenous origin and natural antisense small interfering RNAs (siRNAs) into 22-nt primary siRNAs (Borsani et al, 2005;Xie et al, 2004). DCL2 is mainly involved in antiviral defence; however, there is mounting evidence that its role is masked by DCL4 activity, as it has been clearly demonstrated that DCL2 is also involved in transitivity and the RNA decoy mechanism (Mlotshwa et al, 2008;Parent et al, 2015;Qin et al, 2017;Taochy et al, 2017;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%